Pensões por morte no Brasil: uma análise do impacto financeiro considerando variações demográficas sobre a pensão por morte do Regime Geral de Previdência Social - Nascimento, Michelly Vieira do (2021)
Demographic transition refers to changes in fertility and mortality rates, from high to low levels, and with that there is a change in the age structure of the population. As a result, at the end of this process, there is an older population. But during the demographic transition there are also social changes, especially during the second demographic transition with effects on fertility, for example. The General Social Security System, as it is based on the simple pay-as-you-go financial system, is sensitive to demographic changes and therefore has to adapt periodically to meet its future obligations, referring to payment of benefits, such as the death pension, which it guarantees an income to the insured's dependents when the insured dies. As the class of dependents includes mostly children and spouses, it is expected that changes in fertility, mortality and nuptials will affect the total expenditure on granting this benefit. Therefore, this study aims to estimate the future financial impact on pensions for death granted by the General Social Security System derived from changes in demographic variables. For this, the function representing the average burden on dependents generated by the death of the insured was calculated, in which it was found that variations in fertility, mortality and nuptiality (demographic variants) modify how the pension expenditure is granted over the ages of the insured.